Islamic arms and armor in the Metropolitan Museum of Art - Alexander, David G. (The Metropolitan Museum of Art, 2015)
"Armor and weaponry were central to Islamic culture not only as a means of conquest and the spread of the faith, but also as symbols of status, wealth, and power. The finest arms were made by master craftsmen working with the leading designers, goldsmiths, and jewelers, whose work transformed utilitarian military equipment into courtly works of art. This book reveals the diversity and artistic quality of one of the most important and encyclopedic collections of its kind in the West. The Metropolitan Museum's holdings span ten centuries and include representative pieces from almost every Islamic culture from Spain to the Caucasus. Presenting 126 objects, each handsomely photographed and richly documented with a detailed description of discussion of its technical, historical, and artistic importance, this overview of the Met's holdings is supplemented by an introductory essay on the formation of the collection, and appendixes on iconography and on Turkman-style armor."